Toxic effect of cadmium on seed germination, growth and biochemical contents of cowpea (Vigna unguiculata l.) plants - Sureshkumar1, A. Natarajan2, P. Vijayarengan2, S. Sharavanan2, *M. Vijayaragavan1, C. Prabhahar3, J. (International Multidisciplinary Research Journal, 2011)
Treatment of cowpea (Vigna unguiculata L.) with different concentrations of cadmium decreased the germination percentage, growth parameters and biochemical contents. The experiment was conducted at Botanical Garden, Department of Botany, Government Arts College, Thiruvannamalai, Tamil Nadu, during the period of January to March 2011. In the pot culture experiment, cowpea plants were analysed on three different sampling (viz., 15th, 30th and 45th) days, in soil amended with various levels of cadmium (viz, 10, 30, and 50 mg kg-1). The inner surfaces of pots were lined with a polythene sheet. Each pot containing 3kg of air dried soil. Six seeds were sown in each pot. All pots were watered to field capacity daily. Plants were thinned to a maximum of three per pots, after a week of germination. Cadmium at all levels (10,30 and 50mg kg-1) tested, decreased the growth parameters such as, root and shoot length, fresh and dry weight of root and shoot, total leaf area and biochemical constituents such as, chlorophyll-a, chlorophyll-b, total chlorophyll and carotenoid contents of cowpea plants compared to untreated plants.